2019
DOI: 10.11646/phytotaxa.416.1.2
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Taxonomy and biology of <em>Cordyceps qingchengensis sp. nov</em>. and its allies</strong></p>

Abstract: Cordyceps qingchengensis sp. nov., growing on a cocooned pupa of a silk moth (Lepidoptera: Bombycidae) and collected from southwestern China, is described, illustrated and compared with allied taxa. The species is morphologically similar to C. bifusispora and C. tenuipes, but can be easily separated from the latter two by the unique host and by branched and thicker stroma. Phylogenetic analyses of single ITS and combined SSU, LSU and TEF1-α datasets indicate that it is closely related to C. bifusispora, C. cic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Considerable changes to the taxonomy of Cordyceps have occurred since the research on entomogenous fungi entered the molecular era. At present, multi-locus phylogenetic analyses have gained importance in delimiting Cordyceps species ( Tasanathai et al, 2016 ; Zha et al, 2019 ; Li et al, 2020 , 2021 ; Wang Y. B. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable changes to the taxonomy of Cordyceps have occurred since the research on entomogenous fungi entered the molecular era. At present, multi-locus phylogenetic analyses have gained importance in delimiting Cordyceps species ( Tasanathai et al, 2016 ; Zha et al, 2019 ; Li et al, 2020 , 2021 ; Wang Y. B. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zha & T.C. Wen were reported by Crous et al (2019) and Zha et al (2019). Thus, Cordyceps now consists of about 80 species.…”
Section: Introductionmentioning
confidence: 94%
“…Song et al (2006) reported the known taxa of Cordyceps from China and their distribution (125 species and 3 varieties). Some new Cordyceps species were reported later from China (Li et al 2008, Liang et al 2008, Yang et al 2009, Cao et al 2010, Chen et al 2013b, Wen et al 2013, Yan & Bau 2014, Yang et al 2015, Zhou et al 2015, Yu et al 2017, Qu et al 2018a, 2018b, Wang et al 2018, Zha et al 2019. Furthermore, some anamorphic species of Cordyceps were also reported (Huang et al 2007, Zou et al 2010, Zhang et al 2013, Chen et al 2013a, 2017a, 2017b.…”
Section: Introductionmentioning
confidence: 99%